EFFECTIVENESS OF ORGANIZING THE PROFESSIONAL ACTIVITIES OF A CIVIL SERVANT: LEGAL PRINCIPLES AND MECHANISMS (Journal of actual problems of jurisprudence, 2025)
This article addresses the issues of improving the legal and institutional foundations of civil service in the context of enhancing the effectiveness of public administration in the post-Soviet space, particularly in the Republic of Kazakhstan. Following the collapse of the Soviet Union, restructuring the state apparatus became a key condition for building a democratic and rule-of-law-based state.The aim of the study is to analyze the factors contributing to effective public administration by clarifying the legal status of civil servants. The main focus areas include civil service reform, improvement of personnel policy, strengthening of professional ethics and accountability, and optimization of the legislative framework based on international experience.The scientific and practical significance of the work lies in demonstrating the role of legal regulation in modernizing the public administration system. The methodology includes comparative legal analysis, examination of normative acts, historical and legal review, and a systematic approach.The research results systematize issues related to the legal status of civil servants, their professional training, ethical standards, and working conditions. The author explores the interconnection between the civil servant’s oath, remote working practices, career advancement, and social guarantees, identifying key mechanisms that affect the functional stability of the state apparatus.This study contributes to the body of knowledge in law, public administration, and civil service. Its findings can be applied in human resource policy development, legislative reforms, and the enhancement of governance culture.Keywords: public administration, legal status, civil service, administrative reform, ethics, human resources, professional development.